Towards a new understanding of Iron Age Caithness (Proceedings of the Society of Antiquaries of Scotland, 2002)
Re-investigation of the nineteenth-century excavations by Sir Francis Tress Barry has initiated a study of three Iron Age roundhouse complexes at Keiss, Caithness. The paper presents the key findings and uses a series of scenarios to explain the observed patterns. The importance of Caithness to understandings of Iron Age Scotland is emphasized and future objectives highlighted.